Specific Characteristics of Types of Incentives in the State Civil Service - Alisher Nasirdinovich Juraev (Genius Journals, 2022)
This article also analyzes various discussions about the types of incentives in the public service. In addition, the article analyzes the framework established by law for the frequency of assessing the effectiveness of the professional activities of civil servants, the appointment of measures to encourage civil servants and the possibility of their subsequent application. This article analyzes the theoretical and legal foundations of the types of incentives in the public service.
Keywords: State civil service; incentives; temporary incentives; privilege